Influence of conditioned media from glial cell cultures on contractility of uterine in rats of different ages - H.V. Nesteruk; N.M. Alabedalkarim; N.A. Komaromi; N.О. Tkachenko; O.S. Protsenko; Y.I. Lehach (Publishing House TRILIST, 2022)
Background. The physiological regulation of the uterine contractile activity changes with age, which leads to an increased number of prolonged labor and emergency caesarean sections in women giving birth at the age of 35+. One of the modern approaches to correct the function of the reproductive system is the use of from cell cultures. CM from glial cell culture contains neurotrophic factors that play an important role in maintaining the contractile function of the uterus. Current cell culture technologies include cryopreservation. Objective: to research experimentally the effect of CM obtained from intact and cryopreserved cultures of glial cells on the contractile activity of the uterus in rats of different reproductive ages. Materials and methods. The monolayer cell culture was obtained from the dorsal root ganglia of neonatal piglets and cryopreserved in the presence of cryoprotectant dimethyl sulfoxide. CM from native and cryopreserved cultures were collected for 28 days, after which fractions with a molecular weight of < 30 kDa were obtained from them by ultrafiltration. Rats at the age of 6 and 14 months, which corresponds to reproductive age and late reproductive age (LRA), were intraperitoneally injected with 0.2 ml of media from intact (ICM) or cryopreserved (CCM) cultures for 9 days. On the 30th - 32nd day after the end of the administration of CM animals were slaughtered and the uterine contractile activity was determined by the organ bath method, the relative area of myometrium and density of myocytes by histological method, the average area of labeling with specific antibodies to smooth muscle actin by immunohistochemical method. The statistical significance of differences was assessed by the Mann-Whitney test. Results. It was found that spontaneous, OT-, and KCl-induced tension of isometric contraction of the uterus in intact LRA rats decreased by 19, 20, and 14%, respectively, compared with intact reproductive aged animals. After the introduction of ICM and CCM in LRA animals, normalization of isometric contraction parameters was observed. This effect was realized against the background of an increase in the area of the myometrium, the density of myocytes, and actin expression. Conclusions. Intra-abdominal administration of CM from glial cell culture increases the uterine contractile activity in LRA rats. This effect is realized by increasing the relative area of the myometrium, the density of myocytes, and the area of expression of smooth muscle actin. The effect of media from intact and cryopreserved cultures on the contractile activity of the uterus was similar, which makes it possible to use low-temperature culture storage technologies to obtain CM without losing its biological effect.